Clinical, Pathological, and Molecular Characteristics of CpG Island Methylator Phenotype in Colorectal Cancer: A Systematic Review and Meta-analysis - Advani, Shailesh M. (Transl Oncol, 2018)
BACKGROUND: CpG island methylator phenotype (CIMP) tumors, comprising 20% of colorectal cancers, are associated with female sex, age, right-sided location, and BRAF mutations. However, other factors potentially associated with CIMP have not been robustly examined. This meta-analysis provides a comprehensive assessment of the clinical, pathologic, and molecular characteristics that define CIMP tumors. METHODS: We conducted a comprehensive search of the literature from January 1999 through April 2018 and identified 122 articles, on which comprehensive data abstraction was performed on the clinical, pathologic, molecular, and mutational characteristics of CIMP subgroups, classified based on the extent of DNA methylation of tumor suppressor genes assessed using a variety of laboratory methods. Associations of CIMP with outcome parameters were estimated using pooled odds ratio or standardized mean differences using random-effects model. RESULTS: We confirmed prior associations including female sex, older age, right-sided tumor location, poor differentiation, and microsatellite instability. In addition to the recognized association with BRAF mutations, CIMP was also associated with PIK3CA mutations and lack of mutations in KRAS and TP53. Evidence of an activated immune response was seen with high rates of tumor-infiltrating lymphocytes (but not peritumoral lymphocytes), Crohn-like infiltrates, and infiltration with Fusobacterium nucleatum bacteria. Additionally, CIMP tumors were associated with advance T-stage and presence of perineural and lymphovascular invasion. CONCLUSION: The meta-analysis highlights key features distinguishing CIMP in colorectal cancer, including molecular characteristics of an active immune response. Improved understanding of this unique molecular subtype of colorectal cancer may provide insights into prevention and treatment.